Answer:
Explanation:
1.
y=mx+b
slope=m=3 (4,2)
Hence y=3x+b (1)
We substitute valueы of x=4 and y=2 into the equation (1):
2=3(4)+b
2=12+b
2-12=12+b-12
-10=b
Thus, b=-10
Hence y=3x-10
2.
y=mx+b
slope=m=-2 (0,3)
Hence y=-2x+b (1)
We substitute valueы of x=0 and y=3 into the equation (1):
3=-2(0)+b
3=0+b
3=b
Thus, b=3
Hence y=-2x+3
3.
y=mx+b
slope=m=-1 (1,-7)
Hence y=-x+b (1)
We substitute valueы of x=4 and y=2 into the equation (1):
-7=-(1)+b
-7=-1+b
-7+1=-1+b+1
-6=b
Thus, b=-6
Hence y=-x-6
And so on ...